The Influence of Social Media Influencers on Purchase Intention with Brand Awareness, Brand Image, and Brand Trust as Mediating Variables in Surabaya - Wardhani, Yustika Puspita; Susanti, Nanis; Cempena, Ida Bagus (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Social media influencers are individuals who use their social media accounts to share their experiences or reviews with their followers. They have the ability to influence the purchase intentions and purchasing decisions of others through the social media used. Social media influencers also help businesses in building brand awareness. In addition to brand awareness, the profile and good reputation of social media influencers will also improve the brand image and brand trust of a brand so that it will increase purchase intention. This research can be used to help businesses about the importance of the role of social media influencers in the digital era as a strategy in marketing products or services sold to increase brand awareness, brand image and brand trust.This study explains the effect of brand awareness, brand image and brand trust in mediating social media influencers on purchase intention in Surabaya. This research was conducted in the city of Surabaya with a sample of 170 people selected using non-probability sampling techniques. The survey was distributed online through the Google Form platform. The findings in this study reveal that social media influencers have a significant effect on brand awareness, brand image and brand trust. Brand awareness, brand image and brand trust have a significant effect on purchase intention. In addition, brand awareness, brand image and brand trust have a significant effect on purchase intention.